Partial Purification and Properties of the Pyruvate-Uridine Diphospho-N-Acetylglucosamine Transferase from Staphylococcus epidermidis - Wickus, Gary G. (1973)
A method for the partial purification of the pyruvate-uridine-diphospho-N-acetylglucosamine transferase from Staphylococcus epidermidis is presented. Some properties of the enzyme are discussed.